2010
DOI: 10.4209/aaqr.2010.04.0028
|View full text |Cite
|
Sign up to set email alerts
|

Gas/Particle Partitioning of Dioxins in Exhaust Gases from Automobiles

Abstract: This study investigates distributions of polychlorinated dibenzo-p-dioxin and polychlorinated dibenzofuran (PCDD/F) congeners in the exhaust gases of gasoline-and diesel-fueled vehicles. 6 sport utility vehicles (SUVs), 6 diesel passenger vehicles (DPVs), and 3 heavy duty diesel vehicle (HDDV) were examined using chassis dynamometer tests for measuring vehicular dioxin emissions. The mean PCDD/F I-TEQ emission factors were 0.101, 0.0688 and 0.912 ng I-TEQ/km for the SUVs, DPVs and HDDV, respectively. Highly ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 21 publications
1
28
0
1
Order By: Relevance
“…The X/E ratio was calculated for each sampling site, and the geometric mean and geometric standard deviation of the X/E ratios for TC, DBP and NT are 2.9 and 1.3; 2.8 and 1.3; and 2.3 and 1.2, respectively, were determined. In fact, characteristics of traffic-related VOC emissions are different from those of traffic-related aerosols (Chakraborty, A. and Gupta, T. 2010;Cheng et al, 2010;Chuang et al, 2010aChuang et al, , 2010bPawar et al, 2010;Shen et al, 2010;Wu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The X/E ratio was calculated for each sampling site, and the geometric mean and geometric standard deviation of the X/E ratios for TC, DBP and NT are 2.9 and 1.3; 2.8 and 1.3; and 2.3 and 1.2, respectively, were determined. In fact, characteristics of traffic-related VOC emissions are different from those of traffic-related aerosols (Chakraborty, A. and Gupta, T. 2010;Cheng et al, 2010;Chuang et al, 2010aChuang et al, , 2010bPawar et al, 2010;Shen et al, 2010;Wu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The results vary from 7.9 to 12, 0.71 to 0.78 and 0.46 to 1.3 ng I-TEQ/km for the light duty vans RK1, RK2 and the passenger car, respectively. These values are slightly higher or on the same order of the highest available published data: 1.3-9.5 ng I-TEQ/km [7], 0.72-9.5 ng I-TEQ/km [9], 0.91 ng I-TEQ/km [24] and 1.7 ng I-TEQ/km [26]. Tables S7 and S8 of Concerning test 3 (cold conditions) and test 4 (warm conditions), which were carried out 2 days apart, it can be observed that the emission of PCDD/Fs was higher in the former than the latter.…”
Section: Methodsmentioning
confidence: 59%
“…In all runs, the concentration of PCDDs in exhaust gases exceeds that of PCDFs. Table S3, we see that several authors [17,19,24,27] In all runs, the PCDD contribution to I-TEQ is greater than that of the PCDFs. Figure 2 The TEQ-weighted congener distribution of the diesel passenger car is shown in Figure 3 Moreover, RK2 belongs to Euro 4 whereas RK1 belongs to Euro 3.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…Chuang et al, 30 using the same driving cycle than this study, obtained average emission of 101 pg I-TEQ km À1 and standard deviation of 64.3 pg I-TEQ km À1 . Marklund et al, cited by Geueke et al, 31 estimated that the emission rate of total PCDD/F in catalyzed vehicles fueled with nonleaded gasoline was of the order of 0.36 I-TEQ pg km À1 .…”
mentioning
confidence: 99%